Naked management bare essentials for motivating the X-generation at work - Muchnick, Marc (St. Lucie Press, 1996)
Offers practical guidelines for managers who need to deal with motivating the 'X-Generation'. This title helps to learn the critical tools both managers and younger employees need to put to use in order to create and maintain a successful workplace environment. It includes case examples of PepsiCo, Ritz-Carlton hotels, NationsBank, and Kinko's.